Effects of vertical hydrodynamic mixing on photomineralization of dissolved organic carbon in arctic surface waters. Issue 4 (25th March 2019) - Li, Angang; Aubeneau, Antoine F.; King, Tyler; Cory, Rose M.; Neilson, Bethany T.; Bolster, Diogo; Packman, Aaron I.
Abstract : Conceptual and numerical models were developed to assess the importance of vertical hydrodynamic mixing on depth-integrated photomineralization rates. Abstract : Photomineralization, the transformation of dissolved organic carbon (DOC) to CO2 by sunlight, is an important source of CO2 in arctic surface waters. However, quantifying the role of photomineralization in inland waters is limited by the understanding of hydrologic controls on this process. To bridge this gap, this study evaluates mixing limitations, i.e., whether and by how much vertical mixing limits the depth-integrated photomineralization rate, in freshwater systems. We developed a conceptual model to qualitatively assess mixing limitations across the range of light attenuation and hydrologic conditions observed in freshwaters. For the common case of exponential light attenuation over depth, we developed a mathematical model to quantify mixing limitation, and used this model to assess a range of arctic freshwater systems. The results demonstrate that mixing limitations are important when there is significant light attenuation by suspended sediment (SS), which is the case in some arctic, boreal and temperate waters. Mixing limitation is pronounced when light attenuation over depth is strong and when the photomineralization rate at the water surface exceeds the vertical mixing rate. Arctic streams and rivers have strong vertical mixing relative to surface photomineralization, such that model results demonstrate no mixing limitation regardless of how much SS is present. Our analysis indicates that well-mixed assumptions used in prior work are valid in many, but not all, arctic surface waters. The effects of mixing limitations in reducing the photomineralization rate must be considered in arctic lakes with high SS concentrations.